Universal data compression based on approximate string matching - Sadeh, Ilan (Zielona Góra: Uniwersytet Zielonogórski)
Two practical source coding schemes based on approximate string matching are proposed. One is an approximate fixed-length string matching data compression combined with a block-coder based on the empirical distribution, and the other is an LZ-type quasi-parsing method by approximate string matching. A lemma on approximate string matching, which is an extension of the Kac Lemma, is proved.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka